SIMULATED ANNEALING INVERSION OF MULTIMODE RAYLEIGH WAVE DISPERSION CURVES FOR GEOLOGICAL STRUCTURE - Beaty K.S.; Schmitt D.R.; Sacchi M. (My University, 2002)
Simulated annealing was used to invert fundamental and higher-mode Rayleigh wave dispersion curves simultaneously for an S-wave velocity profile. The inversion was applied to near-surface seismic data (with a maximum depth of investigation of around 10 m) obtained over a thick lacustrine clay sequence. The geology was described either in terms of discrete layers or by a superposition of Chebyshev polynomials in the inversion and the contrasting results compared. Simulated annealing allows for considerable flexibility in model definition and parametrization and seeks a global rather than a local minimum in a misfit function. It has the added advantage in that it can be used to determine uncertainties in inversion parameters, thereby highlighting features in an inverted profile that should be interpreted with caution. Results show that simulated annealing works well for the inversion of multimodal near-surface Rayleigh wave dispersion curves relative to the same inversion that employs only the fundamental mode.